Multiparametric MRI for local staging in patients with suspected muscle-invasive bladder cancer: study protocol for a multicentre, non-inferiority randomised controlled trial (the BladParadigm study) - Lambertus ALM Kiemeney; Janneke PC Grutters; Erik J.R.J. van der Hoeven; Janneke P.C. Grutters; Antoine G van der Heijden; Sebastiaan W van Koeverden; Lisa MC van Hoogstraten; Maarten de Rooij; Marloes van der Leest; Arnold Baars; Thierry N. Boellaard; Joost L. Boormans; et al. (BMJ Open)
Introduction Muscle-invasive bladder cancer (MIBC) is an aggressive type of cancer. About 50% of patients will die from the disease within 5 years despite radical treatment. This implies that in many patients, the disease has already spread at the time of radical treatment, even though imaging shows no signs of metastasis. We hypothesise that the standard local staging method, transurethral resection of the bladder tumour (TURBT), is partly responsible for tumour cell spread. Furthermore, TURBT (and re-TURBT in many patients) contributes to a significant delay to definitive therapy. The aim of this randomised study is to determine whether multiparametric MRI (mpMRI) of the bladder, in combination with a single outpatient bladder tumour biopsy for histological confirmation, is a safer, faster, less costly and, therefore, more cost-effective diagnostic pathway than TURBT to detect or rule out MIBC.Methods and analysis BladParadigm is a two-arm multicentre randomised controlled trial (RCT) conducted in the Netherlands. Over a 3-year period, patients with clinically suspected MIBC without evidence of metastases will be recruited and randomised 1:1 to either TURBT or 3-Tesla mpMRI with same-day outpatient bladder biopsy. The Vesical Imaging Reporting and Data System (VI-RADS) will be used to standardise mpMRI reporting. Patients will undergo definitive treatment based on the results of the TURBT or mpMRI. The study is powered to demonstrate that the mpMRI-based strategy is at least non-inferior to standard TURBT in patients treated with radical cystectomy alone, assuming a relative hazard of 0.55. The required sample size is 360 patients (180 TURBT, 180 mpMRI). The primary outcome is 2-year progression-free survival. Progression will be assessed by imaging, according to the current standard of care. Secondary outcome measures are time to definitive treatment, quality of life (EuroQol 5D-5L), healthcare costs and cost-effectiveness.Ethics and dissemination This study has received ethical approval from the Medical Ethical Committee Oost-Nederland (NL83685.091.23). All participants will provide written informed consent prior to inclusion. Findings of this study will be disseminated through peer-reviewed, open-access publications, presentations at scientific conferences and stakeholder briefings.Trial registration number NCT05779631.